PENGEMBANGAN MULTIMEDIA INTERAKTIF UNTUK MENULIS PUISI DENGAN MODEL PROJECT BASED LEARNING (PjBl) PADA SISWA KELAS V SEKOLAH DASAR - Muhammad Hanafi; Desyandri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and implement poetry writing instruction using the Project Based Learning (PjBL) model by utilizing technology-based interactive media, namely Canva and Quizizz. The research method used is the ASSURE development model, which focuses on designing instruction according to students’ characteristics. The results show that the use of the PjBL model supported by technology-based interactive media can increase students’ learning motivation and help them better understand the process and structure of poetry writing. Therefore, the implementation of PjBL assisted by Canva and Quizizz can be an effective alternative learning approach to improve elementary school students’ poetry writing skills.